2010
DOI: 10.1007/s11199-010-9875-2
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Child and Father-Child Interactional Synchrony in Dyadic and Triadic Interactions

Abstract: Patterns of interactional synchrony were compared in mother-child and father-child dyads during dyadic and triadic interactions. Forty-two dual-earner families from the French province of Québec, Canada, participated in the study with their 32 months-old child. Parent-child interactions were coded using a taxonomy including the social partners' physical proximity, visual and body orientation, and dyadic involvement. Analyses show similar patterns of interactional synchrony in mother-child and father-child dyad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 71 publications
3
31
0
3
Order By: Relevance
“…However, mothers are more responsive and affect than fathers were. The results from the current study are consistent with the results of some previous studies (Chiarello et al, 2006;Kochanska & Aksan, 2004;Mendonça et al, 2011;Power, 1985;Wilson & Durbin, 2013) that indicated that mothers were rated as more responsive to their children than were fathers. For example, a study carried out by Kochanska and Aksan (2004) concluded that, although children were equally responsive to and playful with both parents, mothers were more responsive than fathers during play sessions, whereas the results of both parents were similar in terms of achievement orientation, affect/animation, and directiveness (Chiarello et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, mothers are more responsive and affect than fathers were. The results from the current study are consistent with the results of some previous studies (Chiarello et al, 2006;Kochanska & Aksan, 2004;Mendonça et al, 2011;Power, 1985;Wilson & Durbin, 2013) that indicated that mothers were rated as more responsive to their children than were fathers. For example, a study carried out by Kochanska and Aksan (2004) concluded that, although children were equally responsive to and playful with both parents, mothers were more responsive than fathers during play sessions, whereas the results of both parents were similar in terms of achievement orientation, affect/animation, and directiveness (Chiarello et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Some of these research studies, which focused on mother-child versus father-child interaction (e.g., Chiarello, Huntington, & Bundy, 2006;Girolametto & Tannock, 1994;Kochanska & Aksan, 2004;Mendonça, Cossette, Strayer, & Gravel, 2011;Power, 1985;Wilson & Durbin, 2013), indicated that mothers play a more dominant role in promoting and supporting their children's development than do fathers. Similar findings reported by Wilson and Durbin (2013) revealed that mothers were more responsive to their child as well as more involved in social and emotional interaction with them, whereas fathers displayed more control and discipline in relation to their child's behavior.…”
mentioning
confidence: 99%
“…The time series of body movements on a second scale is usually much less stable or uniform in the real world than in a laboratory setting [11]. That is, in daily situation, it would be difficult to evaluate the quality of people's communication and to support the communication from the viewpoint of second-scale coevolution like many previous studies [13]- [16], [22]- [29], [37]- [39]. Therefore, if the over-second-scale coevolution between people can be seen in daily situation, the evaluation and support of people's communication would be developed.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory settings, various research psychologists had already verified interpersonal coordination of body movements [13]- [16]. The interpersonal coordination of body movements between people is coevolution on millisecond or second scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation